GDP Per Capita and Protest Activity: A Quantitative Reanalysis. (October 2018) - Korotayev, Andrey; Bilyuga, Stanislav; Shishkina, Alisa
Our research suggests that the relation between GDP per capita and sociopolitical destabilization is not characterized by a straightforward negative correlation; it rather has an inverted U-shape. The highest risks are typical for the countries with intermediate values of GDP per capita, not the highest or lowest values. Thus, until a certain value of GDP per capita is reached, economic growth predicts an increase in the risks of sociopolitical destabilization. This positive correlation is particularly strong ( r = .94, R 2 = .88) and significant for the intensity of antigovernment demonstrations. This correlation can be observed in a very wide interval (up to 20, 000 of international 2014 dollars at purchasing power parities [PPPs]). We suggest that it is partially accounted for by the following regularities: (a) GDP growth in authoritarian regimes strengthens the pro-democracy movements, and, consequently, intensifies antigovernment demonstrations; (b) in the GDP per capita interval from the minimum to $20, 000, the growth of GDP per capita correlates quite strongly with a declining proportion of authoritarian regimes and a growing proportion of intermediate and democratic regimes; and, finally, (c) GDP growth in the given diapason increases the level of education of the population, which, in turn, leads to a higher intensity of antigovernment demonstrations.